A Multicenter Prospective Study on the Use of a Mandibular Advancement Device in the Treatment of Obstructive Sleep Apnea - Eduardo Anitua; Pedro Mayoral; Gabriela Zamora Almeida; Joaquín Durán-Cantolla; Mohammad Hamdan Alkhraisat (MDPI AG, 2023)
The main objective of this prospective study was the evaluation of 1 mm step titration of mandible advancement in the success of treating obstructive sleep apnea (OSA). For that, a multicenter prospective study was designed to recruit patients with OSA who were eligible to receive a mandibular advancement device. Gradual titration of mandibular advancement (steps of 1 mm) from maximum intercuspidation was performed to determine the optimal mandibular advancement (highest reduction in the apnea-hypopnea index (AHI)). The principal variable was the percentage of patients where a reduction ≥50% of the AHI was achieved at the end of the titration phase. A total of 102 patients participated in this study. Fifty-six percent of the participants were males and 67% had a BMI ≥ 25 kg/m2. Most of the patients (79%) had an age ≥ 50 years and the majority (74%) were either non-smokers or ex-smokers. Excessive daytime sleepiness was reported by 40% of the patients. The mean AHI at baseline was 20.6 ± 12.7 events/h. The mean advancement of the mandible was 3.1 ± 1.6 mm. The device achieved a reduction in the AHI in 93% of the patients and success (≥50% reduction in the AHI) in 69% of the patients. Success was achieved in 50%, 81.6%, and 73.3% of the patients with mild, moderate, and severe OSA, respectively. Decreasing the magnitude of mandibular advancement could be possible by controlling the vertical mouth opening and step-by-step titration.